Dynamics of school curriculum integration: interdisciplinarity in the production of knowledge - Peñuela, Diana (Universidad Pedagógica y Tecnológica de Colombia, 2021)
It’s undeniable that changes are being made in the dynamics of curriculum integration in the contemporary school, not only because it is a requirement for changes in the modes of knowledge production at the social level (Gibbons and Others, 1997) or because they are part of the demands of going into questioning discipline, but because they are also transformations that are already being mobilized as neural axes of education policy both at the national and district level for at least a decade.  These dynamics definitely involve a complexization of school knowledge, its production and / or appropriation in our schools, at least from a theoretical-conceptual discussion and it is interesting that the educational policy enables this type of approach. In this context of discussion, this article aims to: (a) mobilize discussions around the contemporary configuration of school knowledge from integration processes; (b) to position discussions around the entry of interdisciplinarity into such processes; c) bet on the possibility of thinking about the models of curriculum integration in both forms of completion of school knowledge and (d) conducting a preliminary analysis of the models of curricular integration at national and district level.